Epidemiologia molecular dos vírus dengue em Goiânia-GO, 1994 - 2006: vigilância laboratorial e caracterização dos sorotipos circulares - FÉRES, Valéria Christina de Rezende (2008)
Nowadays, dengue constitute the major public health problem, because is relevant cause of illness and death between thousands people that resident in the tropical and subtropical regions in world. The dengue virus is classified as four serotypes (DENV-1, 2, 3 and 4) according to antigenic differences and characterized intra-typical groups called genotypes. The laboratorial surveillance enables the diagnostic confirmation of dengue infection and monitoring serotypes circulating through the routine diagnostic techniques. Recently, the use molecular techniques has contributed to characterize and monitoring of the genotypes potentially virulent during epidemic and knowledge of biology of dengue virus. This thesis was organized in an introduction section, that include a literature review on dengue, and two manuscripts that describing the research conducted with focus on laboratory diagnostic and molecular epidemiology. The first manuscript entitled Laboratorial Surveillance of Dengue Virus in Central-Brazil, 1994-2003, was published at Journal of Clinical Virology, 2006 37 (3): 179-83. In this study we present the results of the virological surveillance for dengue cases conducted in the city of Goiânia (~1,200,000 population) from 1994 to 2003. Suspected cases were from the main public infectious disease reference hospital and outpatient clinics covering the metropolitan area. Serological and virus isolation tests were conduced at the regional reference laboratory. Our objective was to report dengue circulating serotypes from 1994 to 2003 and the role of distinct serotypes on dengue clinical outcomes in Central Brazil and to characterize serotypes and genotypes by reverse transcriptase PCR (RT-PCR) and by restricted site-specific PCR (RSS-PCR) patterns in selected samples. Laboratory surveillance identified mainly DEN-1 serotype from 1994 to 2002 shifting to a high circulation of DEN-3 in 2003. The adults (87,4%) were the most affected group and dengue fever accounted for the majority of the cases. Diagnosis of dengue was confirmed in ~50% of the suspected and enhanced by RT-PCR. RSS-PCR patterns for DEN-1 and DEN-3 corresponded to the circulating subtypes in the country. The infection DENV-3 did not suggest a major role of infecting DEN-3 in increasing disease severity during its first-year spread in Central Brazil. The second manuscript, to be submitted for publication is entitled: Epidemiologia Molecular do Vírus Dengue tipo 3 em Goiânia GO, 2005-2006. The objective of this manuscript was to characterize the DENV-3 genotype circulating isolated from well-characterized clinical and laboratory samples in Goiânia-GO/Brasil. Seven samples had sequences of the prM/M/E region obtained and comparative analysis was performed with the reference strains. The results showed the homology of the genomics sequences with genotype III strains. The nucleotide identity of the all the samples varied from 97.0% to 99.6% and the amino acid sequences from 97.5% to 99.5%. The analysis of the nucleotide sequence revealed silent mutation and 14 amino acid changes in the protein deduced from gene prM/M/E. In conclusion, the study confirms that the strains of DENV-3 in Central Brazil relate to genotype III. The genomic changes along Domain III of the protein E were observed, which could affect the pathogenicity, but were not consistent between samples of DCC and DHF. Samples of patients with dengue fever had mutations related to viral attenuation. More investigation is necessary to evidence of genomic changes found in relationship with clinical forms.